2023
DOI: 10.3390/cimb45040209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Internal Exposure of Radioactive 56MnO2 Particles on the Lung in C57BL Mice

Abstract: The investigation of the radiation effects of the atomic bombing in Hiroshima and Nagasaki has revealed concerns about the impact of the residual radioactive dust produced in the soil. Manganese-56 is one of the major radioisotopes produced by neutrons from the bomb; hence, we previously examined the biological effects of manganese dioxide-56 (56MnO2) in Wistar rats, in which significant changes were found in the lung. In the present study, ten-week-old male C57BL mice were exposed to three doses of radioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The gene expression of Aqp1 increased in pulmonary edema models, whereas the expression of Aqp1 and Aqp5 decreased in acute lung injury models [31][32][33]. In our previous study in-volving C57BL mice, 56 MnO 2 exposure resulted in a late increase in the expression of Aqp1, indicating pathophysiological alterations without obvious histological changes [5]. This study confirmed the late effects of 56 MnO 2 exposure on Aqp1 expression as Aqp1 increased 65 days after exposure in the Mn56 × 3 group but not in the Co60 group.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The gene expression of Aqp1 increased in pulmonary edema models, whereas the expression of Aqp1 and Aqp5 decreased in acute lung injury models [31][32][33]. In our previous study in-volving C57BL mice, 56 MnO 2 exposure resulted in a late increase in the expression of Aqp1, indicating pathophysiological alterations without obvious histological changes [5]. This study confirmed the late effects of 56 MnO 2 exposure on Aqp1 expression as Aqp1 increased 65 days after exposure in the Mn56 × 3 group but not in the Co60 group.…”
Section: Discussionmentioning
confidence: 84%
“…Possible radionuclides activated by atomic bombs' neutron beams are 24 Na, 28 Al, 31 Si, 32 P, and 56 Mn [4]. Because 56 Mn is a significant residual radiation source produced by atomic bombs, we investigated the biological effects of 56 MnO 2 on laboratory rats and mice [5,6]. Our studies suggested that exposure to 56 MnO 2 particles induced more prominent physiological responses than external γ-irradiation in both rats and mice, although mice were less sensitive to internal exposure than rats [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations